Mammal predation by an ariid catfish in a dryland river of Western Australia. (December 2016) - Kelly, Erin; Travouillon, Kenny J.; Keleher, James; Gibson-Kueh, Susan; Morgan, David L.
Abstract: The presence of the spinifex hopping mouse Notomys alexis in the diet of lesser salmon catfish Neoarius graeffei from the Ashburton River, Western Australia, is reported for the first time. The consumption of terrestrial mammals by Australian freshwater fishes is widely considered to be an infrequent occurrence, of limited importance to aquatic food webs. However, remains of N. alexis were present within the stomachs of 44% of N. graeffei sampled, constituting approximately 95% of the total stomach contents. These findings suggest that N. graeffei will consume large quantities of terrestrial vertebrates when available, and may represent a valuable energy source for this ecologically important species in dryland rivers. Highlights: The stomach contents of Neoarius graeffei from a dryland river were examined during the early dry season. Remains of spinifex hopping mice Notomys alexis were found within the stomachs of 44% of N. graeffei sampled. High rates of terrestrial vertebrate consumption by N. graeffei is likely a response to temporally available resources. Terrestrial vertebrate subsidies may be important for N. graeffei, and food webs in Australian dryland rivers.